Mitigating noise-induced hearing loss after blast injury. (April 2019) - Muzaffar, SJ; Orr, L; Rickard, RF; Coulson, CJ; Irving, RM
Introduction: Whilst hearing injuries are not life threatening they may have a profound impact on the victim's ability to understand and interact with the world around them. Noise-induced hearing loss is a common occupational injury and hearing impairment as a consequence of noise and blast exposure remains the most common injury in both war and peace for military personnel. Health and Safety legislation has made an impact and in the future innovative approaches to mitigate against acoustic injury sustained in the work place will be fundamental. For the Armed Forces, noise exposure during conflict is unpredictable. Furthermore, recent events in the UK and elsewhere have highlighted the potential civilian impact of blast injuries on hearing in the acute setting. No well-established protocol for the management of acute, blast-induced hearing injury currently exists. Methods: Narrative review is supported by electronic literature searches of PubMed, Embase and the Cochrane Library. Synthesis of published literature and production of flow charts for the acute setting are part of the Emergency Preparedness, Resilience and Response programme. Results: Whilst there is a lack of high-quality randomised controlled trials, there are a number of studies that may inform our choice of acute management. Animal studies of acute acoustic trauma have shown the potential protective effects of corticosteroids. Human data may be extrapolated from sudden onset sensorineural hearing loss where again there is evidence for the use of corticosteroids. Less certainty exists around the use of other treatments including antioxidants. Intratympanic administration of corticosteroids may be superior to oral administration, particularly in the salvage setting. No evidence exists specifically pertaining to the paediatric population. Conclusion: Prompt identification of any hearing deficit followed by administration of glucocorticoids either orally or via intratympanic preparations is the mainstay of management. Further research is needed to identify the optimum acute management.